2013
DOI: 10.1044/1092-4388(2012/11-0076)
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Efficacy and Intensity for Children With Speech Sound Disorder

Abstract: Preschool children with SSD who received the multiple oppositions approach made significantly greater gains when they were provided with a more intensive dose frequency and when cumulative intervention intensity was held constant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 43 publications
6
97
0
11
Order By: Relevance
“…Within adult motor speech impairments, dose-frequency appears to have no effect when comparing dosefrequencies of two or more sessions per week. However, high dose-frequency phonology treatment was more efficacious than a low dose-frequency treatment (Allen, 2013), suggesting that dose-frequency has different effects across linguistic and motor domains or in children versus adults.…”
Section: Dose-frequencymentioning
confidence: 71%
See 2 more Smart Citations
“…Within adult motor speech impairments, dose-frequency appears to have no effect when comparing dosefrequencies of two or more sessions per week. However, high dose-frequency phonology treatment was more efficacious than a low dose-frequency treatment (Allen, 2013), suggesting that dose-frequency has different effects across linguistic and motor domains or in children versus adults.…”
Section: Dose-frequencymentioning
confidence: 71%
“…For example, Allen (2013) reported that therapy delivered three times weekly was more effective than therapy once a week. However, studies comparing frequencies of two or more sessions a week have tended to report no differences in gains (Spielman et al, 2007;Wambaugh et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, some aspects of clinical practice were not examined in the questionnaire including eclectic approaches to intervention and intensity. Given recent research identifying intensity as critical to progress (Allen, 2013;Williams, 2012), future research is needed to examine this important aspect of practice. Finally, questionnaire data always carry an element of bias -respondents can over-estimate what they do (Adams, Soumerai, Lomas, & Ross-Degnan, 1999).…”
Section: Limitations and Future Researchmentioning
confidence: 98%
“…Due to this higher therapy frequency, the tutees may have perceived a faster improvement of their speech sound proficiency which may have resulted in a higher self-assessed learning success. Moreover, some studies reported better outcomes after more intensive therapy with the same cumulative intervention intensity [27, 28]. As these studies included only children, further research will be necessary to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%